2002
DOI: 10.1034/j.1600-0889.2002.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ecosystem-atmosphere exchange of energy and mass in a European Russian and a central Siberian bog II. Interseasonal and interannual variability of CO2 fluxes

Abstract: Net ecosystem–atmosphere exchange of CO2 (NEE) was measured in two boreal bogs during the snow‐free periods of 1998, 1999 and 2000. The two sites were located in European Russia (Fyodorovskoye), and in central Siberia (Zotino). Climate at both sites was generally continental but with more extreme summer–winter gradients in temperature at the more eastern site Zotino. The snow‐free period in Fyodorovskoye exceeded the snow‐free period at Zotino by several weeks. Marked seasonal and interannual differences in NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
100
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 60 publications
18
100
0
2
Order By: Relevance
“…the transformation of these stands from sources into sinks of CO 2 or vice versa. This corresponds to the observed results that an ecosystem being close to the equilibrium actually can be sink or source of CO 2 in different years depending on weather conditions (e.g., Arneth et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…the transformation of these stands from sources into sinks of CO 2 or vice versa. This corresponds to the observed results that an ecosystem being close to the equilibrium actually can be sink or source of CO 2 in different years depending on weather conditions (e.g., Arneth et al, 2002).…”
Section: Discussionsupporting
confidence: 80%
“…Some studies identified WTD as the major control on net ecosystem CO 2 exchange (NEE) or its component fluxes of photosynthesis [gross ecosystem exchange (GEE)] and total ecosystem respiration (R eco ) (e.g., Arneth et al, 2002). Other studies concluded that WTD was a less important control than light, and air (T air ) or soil temperature (T soil ) (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…These parameters were held constant across the domain. We calibrated these parameters using CO 2 flux observations for the year 2000 from the Zotino Bog eddy covariance tower (Arneth et al, 2002), denoted with a yellow star in Fig. 1.…”
Section: Biogeochemistrymentioning
confidence: 99%